Nonequilibrium thermodynamics : transport and rate processes in physical, chemical and biological systems - Demirel, Yasar (Elsevier, 2007)
Natural phenomena consist of simultaneously occurring transport processes and chemical reactions. These processes may interact with each other and lead to instabilities, fluctuations, and evolutionary systems. The objective of this book is to explore the unifying role of thermodynamics in natural phenomena. Nonequilibrium Thermodynamics, Second Edition analyzes the transport processes of energy, mass, and momentum transfer processes, as well as chemical reactions. It considers various processes occurring simultaneously, and provides students with more realistic analysis and modelling by accounting for possible interactions. This second edition updates and expands most of the chapters of the first edition by focusing on the balance equations of mass, momentum, energy, and entropy together with the Gibbs equation for coupled processes of physical, chemical, and biological systems. Every chapter contains examples practical problems to be solved. This book will be effective in senior and graduate education in chemical, mechanical, systems, biomedical, tissue, biological, and biological systems engineering, as well as physical, biophysical, biological, chemical, and biochemical sciences. * Will help readers in understanding and modelling some of the coupled and complex systems, such as coupled transport and chemical reaction cycles in biological systems * Presents a unified approach for interacting processes - combines analysis of transport and rate processes * Introduces the theory of nonequilibrium thermodynamics and its use in simultaneously occurring transport processes and chemical reactions of physical, chemical, and biological systems * A useful text for students taking advanced thermodynamics courses.